2018
DOI: 10.3233/jad-180240
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Cerebrospinal Fluid Biomarker Profiles in Patients Explored for Cognitive Disorders

Abstract: While A+/N+ patients had the clinical characteristics typically observed in AD, A+/N-patients had a different epidemiological pattern (higher frequency in men, no association with advanced age or lower MMSE). The SNAP profile was less frequent than previously reported in the general elderly population, suggesting that this profile is not a frequent cause of memory impairment in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Gender distribution was equal across groups independent of classification used (by Aβ1-42 and cognitive status or biomarker only). A tendency towards higher representation of male subjects in the A+/T-vs the A+/T+ group was observed which was in line with earlier reports (Paquet et al, 2018). Participants classified as pAD and A+/T+ had lower weight and BMI and participants classified as A−/T− were younger.…”
Section: Demographic Biomarker and Cognitive Characteristicssupporting
confidence: 91%
“…Gender distribution was equal across groups independent of classification used (by Aβ1-42 and cognitive status or biomarker only). A tendency towards higher representation of male subjects in the A+/T-vs the A+/T+ group was observed which was in line with earlier reports (Paquet et al, 2018). Participants classified as pAD and A+/T+ had lower weight and BMI and participants classified as A−/T− were younger.…”
Section: Demographic Biomarker and Cognitive Characteristicssupporting
confidence: 91%
“…In this study we chose not to use the recently proposed A/T/N classification[18, 28] as we have previously showed that some profiles (A-T+N-, A+T+N-) were quite rare, representing less than 1% of the sample [25]. Furthermore, in our data CSF Tau and CSF p-Tau 181 were highly correlated (Spearman coefficient correlation = 0.84, P<0.001).…”
Section: Methodsmentioning
confidence: 63%
“…For the present study, CSF biomarkers from 18 hospitals in and around Paris, France, were aggregated in one biochemistry department. All patients seen between January 1 st 2008 and January 1 st 2018 for whom AD biomarkers from CSF were available were included in the analysis; methods and characteristics of the population have been previously reported elsewhere [25, 26]. The study was approved by the Ethical Committee of Paris University Hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…Within SNAP cases, few studies distinguished A−T+N+ from A+T-N+. A recent survey from a large AD biomarker database showed that 64% of A−N+ cases were T+ [59] . However, this study used high T-tau to define N+, leaving out N+ patients determined by neuroimaging (where atrophy and/or hypometabolism define N+).…”
Section: Discussionmentioning
confidence: 99%